The Effectiveness of the Team Quiz Method in Improving Akidah Akhlak Learning Outcomes at MTs - Muqoddas, Muhammad Imam (Yayasan Lembaga Studi Makwa, 2025)
This study aims to analyze the effectiveness of applying the Team Quiz method in improving the learning outcomes of Aqidah Akhlak among eighth-grade students at MTs Thawalib Putra Padang Panjang, given the persistent problems such as lack of focus, low willingness to ask questions, and uneven achievement of learning indicators. The research employed a quantitative approach with an experimental method, in which the experimental class was treated with the Team Quiz strategy, while the control class used conventional learning methods. The sample consisted of 25 students, and data were analyzed using hypothesis testing with the assistance of SPSS software. The results show a significant influence of the Team Quiz method on improving Aqidah Akhlak learning outcomes, with t = -8.754, df = 25, and sig. (2-tailed) = 0.000 < 0.05, indicating that the alternative hypothesis (H1) was accepted and the null hypothesis (H0) was rejected. The average learning outcomes of the experimental class using Team Quiz were higher than those of the control class, namely 83.40 with a standard deviation of 2.533, demonstrating a substantial difference in academic achievement. The study concludes that the Team Quiz method is effective in fostering student engagement and enhancing understanding of Aqidah Akhlak subject matter. Academically, this research contributes by enriching the literature on participatory-based learning strategies and provides practical insights for educators in optimizing Islamic religious education, particularly Aqidah Akhlak, at the madrasah level.